Literary review and preliminary test design proposal for white shrimp packaging replacement for a shrimp packaging company from USA - Villamarín B., María E. (Zamorano: Escuela Agrícola Panamericana, 2020., 2020)
Shrimps is one of the most consumed seafood products in USA. The shrimp industry faces a big challenge due to short shelf life. One of the main trends in the food industry is the natural products, in which consumers prefer to acquire products that do not use chemical ingredients during their entire process. For this reason, the food industry currently evaluates different types of natural preservatives. One of the natural preservatives that has shown promising results in the meat industry is rosemary extract. In addition, one of the most popular and efficient methods to extend the products shelf life and maintain their quality is Modified Atmosphere Packaging (MAP) and vacuum packaging is one of the most used. A packaging system that includes vacuum atmosphere and rosemary extract is attractive as a fresh product package. During the study, nine different treatments plus three controls were analyzed, rosemary + polybag, rosemary + vacuum packaging, vacuum only and control Polybag in three different white shrimp (Litopenaeus vannamei) presentations (Head-on, Headless, Peeled and deveined). The samples were maintained in refrigeration. The analysis results show that for microbiological control (Total plate count, Total coliforms, Salmonella, Staphylococcus aureus, E. coli,), rosemary extract + polybag and Rosemary extract + vacuum, showed the lower total coliform count at day 6. For color stability, reducing the color change due to oxidation reaction and quality maintenance, reduce of texture, appearance and odor change, rosemary+ vacuum in headless presentation was the best.